2021
DOI: 10.3389/fpsyg.2020.590204
|View full text |Cite
|
Sign up to set email alerts
|

EMDR in Cancer Patients: A Systematic Review

Abstract: Background: Psychological distress is common among patients with cancer, with severe consequences on their quality of life. Anxiety and depression are the most common clinical presentation of psychological distress in cancer patients, but in some cases cancer may represent a traumatic event resulting in posttraumatic stress disorder (PTSD). Currently, Eye Movement Desensitization and Reprocessing (EMDR) therapy is considered an evidence-based treatment for PTSD, but recent studies also showed its effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…The virtual environments and scenarios created in VR can be highly realistic, exposing patients to situations that could trigger their problem behavior or simulate traumatic experiences. Recalling traumatic experiences or memories can be highly effective in treatment, as demonstrated in EMDR therapy ( Portigliatti Pomeri et al, 2021 ). However, it may also lead to heightened psychological distress, which could have unintended consequences on the mental well-being and safety of patients and healthcare providers involved in the VR treatment ( González Moraga et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virtual environments and scenarios created in VR can be highly realistic, exposing patients to situations that could trigger their problem behavior or simulate traumatic experiences. Recalling traumatic experiences or memories can be highly effective in treatment, as demonstrated in EMDR therapy ( Portigliatti Pomeri et al, 2021 ). However, it may also lead to heightened psychological distress, which could have unintended consequences on the mental well-being and safety of patients and healthcare providers involved in the VR treatment ( González Moraga et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a large and complex group of diseases [1] involving a life-altering or potentially life-threatening experience [2,3]. People diagnosed with cancer and patients undergoing cancer-related treatment commonly report increased psychological distress [3], fatigue [4,5], cognitive deficits [6], and physical problems [7]. Cancer is also a serious public health problem [8], associated with economic and financial burden [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even though cancer is a stressful, challenging, and traumatic event [3], this difficult experience may paradoxically have some positive consequences among cancer survivors [16,17]. In fact, Henson et al [18] observed that the growth and positive psychological changes are not an outcome of the event itself, but rather a consequence of several components.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Wesselmann et al., 2012) have also considered the beneficial effect EMDR therapy can have on attachment status and relational trauma. EMDR has also shown promising results for various sample groups such as refugees (Acarturk et al., 2016), cancer patients (Portigliatti Pomeri et al., 2021), children (Rodenburg et al., 2009) and combat veterans (Albright & Thyer, 2010). Reflecting extensive research confirming the effectiveness of EMDR therapy, organisations including the World Health Organisation (World Health Organisation, 2013), the American Psychiatric Association (American Psychological Association, 2017; Ursano et al., 2004), the International Society for Traumatic Stress (Bisson et al., 2019; ISTSS, 2018) and the UK’s National Institute for Clinical Excellence (NICE; NICE, 2018) recommend EMDR as a treatment for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Wesselmann et al, 2012) have also considered the beneficial effect EMDR therapy can have on attachment status and relational trauma. EMDR has also shown promising results for various sample groups such as refugees (Acarturk et al, 2016), cancer patients (Portigliatti Pomeri et al, 2021), children (Rodenburg et al, 2009) and combat veterans (Albright & Thyer, 2010). Reflecting extensive research confirming the effectiveness of EMDR therapy, organisations including the World Health Organisation (World Health Organisation, 2013),…”
Section: Introductionmentioning
confidence: 99%